Medical Acute Complications of Intracerebral Hemorrhage in Young Adults - Riku-Jaakko Koivunen; Elena Haapaniemi; Jarno Satopää; Mika Niemelä; Turgut Tatlisumak; Jukka Putaala (Stroke Research and Treatment)
Background. Frequency and impact of medical complications on short-term mortality in young patients with intracerebral hemorrhage (ICH) have gone unstudied. Methods. We reviewed data of all first-ever nontraumatic ICH patients between 16 and 49 years of age treated in our hospital between January 2000 and March 2010 to identify medical complications suffered. Logistic regression adjusted for known ICH prognosticators was used to identify medical complications associated with mortality. Results. Among the 325 eligible patients (59% males, median age 42 [interquartile range 34–47] years), infections were discovered in 90 (28%), venous thrombotic events in 13 (4%), cardiac complications in 4 (1%), renal failure in 59 (18%), hypoglycemia in 15 (5%), hyperglycemia in 165 (51%), hyponatremia in 146 (45%), hypernatremia in 91 (28%), hypopotassemia in 104 (32%), and hyperpotassemia in 27 (8%). Adjusted for known ICH prognosticators and diabetes, the only independent complication associated with 3-month mortality was hyperglycemia (plasma glucose >8.0 mmol/L) (odds ratio: 5.90, 95% confidence interval: 2.25–15.48, P<0.001). Three or more separate complications suffered also associated with increased mortality (7.76, 1.42–42.49, P=0.018). Conclusions. Hyperglycemia is a frequent complication of ICH in young adults and is independently associated with increased mortality. However, multiple separate complications increase mortality even further.